Non-Koszul quadratic Gorenstein toric rings - Matsuda, Kazunori (MATHEMATICA SCANDINAVICA, 2018)
Koszulness of Gorenstein quadratic algebras of small socle degree is studied. In this paper, we construct non-Koszul Gorenstein quadratic toric ring such that its socle degree is more than 3 by using stable set polytopes.